Determination of the relative configuration of terminal and spiroepoxides by computational methods : advantages of the inclusion of unscaled data - Zanardi, María Marta (2017)
Fil: Zanardi, María Marta. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Argentina